Perjanjian Perkawinan Perampam Dene Dalam Adat Gayo: Kajian, Praktik, Dan Faktor Keberlangsungan - Hanifah Indriyani Anhar (Universitas Merdeka Madiun, 2023)
Customs are considered outdated by the younger generation. However, there are some Gayo customs that are still strong and being maintained. One of them is the marriage agreement of perampam dene in the Gayo custom. Until nowadays, the marriage agreement of perampam dene is still being implemented. Whereas the Indonesian people already have very vital rules regarding marriage agreements. Provisions regarding marriage agreements are contained in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). Based on the results of the study, it is concluded that: first, perampam dene is carried out by the Reje receiving reports and giving advice to the family (temerap mulo). Sarak Opat consults and analyzes the chronology of events. Next, define the actions to solve the problem. Petue and the imem of the village mediate between families to get a reconciliation agreement. If there is a violation, Reje will return to act and deal with it. If it is not completed at the reje level, it continues to the level of mukim, if it is not completed at the mukim level, it can be brought to positive law for customary considerations. Second, the continued implementation of perampam dene is intended to accomplish marital harmony, conformity of perampam dene with Islamic teachings, and create order in society.